2012
DOI: 10.1002/pro.2077
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of thermally induced heat shock protein 27 and 70 expression by bone marrow‐derived mesenchymal stem cells

Abstract: Although bone marrow-derived mesenchymal stem cells (MSCs) are an attractive cell therapy candidate, their potential is limited by poor survival following transplantation. Overexpression of anti-apoptotic heat shock proteins using viral vectors can improve the survival of these cells under stressful conditions in vitro and in vivo. It is also possible to induce heat shock protein expression in many cell types by simply exposing them to a transient, nonlethal elevation in temperature. The response profile of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…This induced the expression of Hsp27 and Hsp70, which was shown to be dependent on the time course of exposure [Moloney et al, 2012].…”
Section: Osteoblast Differentiation and Hsp Expressionmentioning
confidence: 91%
“…This induced the expression of Hsp27 and Hsp70, which was shown to be dependent on the time course of exposure [Moloney et al, 2012].…”
Section: Osteoblast Differentiation and Hsp Expressionmentioning
confidence: 91%
“…Moreover, heat shock pre-treated cells improved global heart function after MI and efficiently reduced cardiomyocyte apoptosis likely by the secretion of heat shock factor (HSF) 1-enriched exosomes [427]. Similarly, short-time exposure of MSCs to elevated temperatures induced the expression of HSPs and decreased apoptotic rates [428,429].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Another factor which has recently been identified is genetic polymorphism affecting the production of cytokines. It was found that the effect of fish oil on cytokine production by human mononuclear cells was dependent on the nature of the polymorphism (308 TNF-α and +252 TNF-β), raising the possibility of identifying those that are most and least likely to experiment specific anti-inflammatory effects of fish oil 12,20 .…”
Section: Ind Vs Pos) (Figure 11mentioning
confidence: 99%
“…The increased expression of these proteins in experimental models for sepsis, shock, critical illness and injury reduces the organ injury, attenuates the pro-inflammatory response and improves survival [19][20] .…”
Section: Ind Vs Pos) (Figure 11mentioning
confidence: 99%